Impact of exchange rate derivatives on stocks in emerging markets - Bernal-Ponce, L. Arturo; Castillo-Ramírez, Claudia Estrella; Venegas-Martínez, Francisco (Journal of Business Economics and Management, 2020)
This paper investigates the effect of derivatives on the relationship between the foreign exchange rate and the stock market. A theoretical model is used to extend the understanding of that relationship. Also, the model is tested with an empirical analysis using the GMM strategy for the Mexican and Brazilian stock markets for the period 2007 to 2019. Findings reveal that in addition to the spot exchange rate, exchange rate futures explain the currency exposure, wherein the derivative effect is the most prominent. The result implies that both risk sources should be considered in the implementation of risk management or macroeconomic policy. The theoretical results are extended by applying them to international portfolio management, proposing a strategy to mitigate foreign exchange exposure with derivatives. This study contributes to the literature by explaining why the minimum variance hedge ratio plays an essential role in the foreign exchange rate and stock market nexus.